Analisis Nilai Tambah Tape Ubi Jalar Ungu pada Agroindustri Tape 25 Bondowoso - Erika Rifkiyah Rahmatillah; Sulistyaningsih Sulistyaningsih; Gema Iftitah Anugerah Yekti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
In developing agricultural-based businesses, such as agribusiness and agro-industry, the agricultural sector can serve as a basis for the growth of other rural economic activities. Sweet potato purple is an agricultural commodity that is widely processed into products. Purple sweet potato tape is the latest innovation in the Bondowoso area. The resilience of the "Tape 25" agro-industry in running its business is to create a breakthrough by creating processed tape products made from purple sweet potatoes. The purpose was to determine the feasibility of the business and the added value of the purple sweet potato tape-making process in the "Tape 25" in Bondowoso. It was carried out in January of this year. The sampling technique uses purposive sampling. The respondents of this study were Bondowoso tape entrepreneurs. This method uses a descriptive and quantitative approach to data collection, namely participation, interviews, and documentation, which are primary and secondary data sources. The research variables analyze the added value of purple sweet potato tape. Data analysis techniques to test business feasibility are the R/C Ratio and using the Hayami formula and table to determine added value.